IVF and IUI in couples with unexplained infertility (FIIX study): study protocol of a non-inferiority randomized controlled trial. Issue 3 (22nd September 2020) - Prentice, Lucy; Sadler, Lynn; Lensen, Sarah; Vercoe, Melissa; Wilkinson, Jack; Edlin, Richard; Chambers, Georgina M; Farquhar, Cynthia M
Abstract: STUDY QUESTIONS: In couples with unexplained infertility and a poor prognosis of natural conception, are four cycles of IUI with ovarian stimulation (IUI-OS) non-inferior to one completed cycle of IVF for the outcome of cumulative live birth? Are four cycles of IUI-OS associated with a lower cost per live birth compared to one completed cycle of IVF? Will four cycles of IUI-OS followed by one complete cycle of IVF result in as many live births at lower cost per live birth, than two complete cycles of IVF? Will four cycles of IUI-OS followed by two complete cycles of IVF result in more live births at lower cost per live birth, than two complete cycles of IVF alone? WHAT IS KNOWN ALREADY: IUI is widely used in the USA, the UK and Europe as a low cost, less invasive alternative to IVF for couples with unexplained infertility. Although three to six cycles of IUI were comparable to IVF in the three major studies carried out to date, gonadotrophin ovarian stimulation was used in the majority of cases, and this also resulted in a high multiple pregnancy rate in some studies. Ovarian stimulation with clomiphene citrate is known to have lower multiple pregnancy rates. STUDY DESIGN, SIZE, DURATION: The FIIX study is a multicentre, open label, parallel, pragmatic non-inferiority randomized controlled trial of 580 couples with unexplained infertility comparing four cycles of IUI-OS with clomiphene citrate and one completed cycle of IVF. Variable block randomization stratified by age and clinic with electronic allocation will be used. PARTICIPANTS/MATERIALS, SETTING, METHODS: Couples with poor prognosis for natural conception and who are eligible for publicly funded fertility treatment in six fertility clinics in New Zealand. STUDY FUNDING/COMPETING INTEREST(S): Auckland Medical Research Fund (3718892/1119003), A+ Trust, Auckland District Health Board (A + 8479), Maurice and Phyllis Paykel Trust (3718514). No competing interests. TRIAL REGISTRATION NUMBER: ACTRN12619001003167. TRIAL REGISTRATION DATE: 15 July 2019 DATE OF FIRST PATIENT'S ENROLMENT: 02/08/2019